Pengaruh Waktu Operasional, Kualitas Pelayanan, Variasi Produk, dan Harga Terhadap Kepuasan Pelanggan (Studi pada Toko Kelontong Kecamatan Lowokwaru Kota Malang) - Yusuf, Haris Muhamad; Slamet, Afi Rachmat; Dianawati, Eris (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of operational time, service quality, product variety and price on customer satisfaction among grocery store buyers. This research uses a quantitative description method. The respondents for this research were 94 respondents as customers at the Lowokwaru District grocery store who were selected using a purposive sampling technique with the maholtra formula. Data collection uses a questionnaire consisting of 2 variables, namely operational time, service quality, product variety, price and customer satisfaction. Data obtained from respondents was analyzed using SPSS (Statistical Program for Social Science). The results of this research show that: (1) Operational time, service quality, product variety and price simultaneously influence customer satisfaction in the study of Madurese grocery store buyers. (2) Operational time has a partial effect on customer satisfaction in the study of Madurese grocery store buyers. (3) Service quality has a partial effect on customer satisfaction in the study of Madurese grocery store buyers. (4) Product variety has a partial effect on customer satisfaction in the study of Madurese grocery store buyers. (5) Price has a partial effect on customer satisfaction in the study of Madurese grocery store buyers. Keywords: Operational Time, Service Quality, Product Variation, Price, Customer Satisfaction